Analysis of spatio-temporal precipitation and temperature variability and trend over Sudd-Wetland, Republic of South Sudan - Zeleke, Tadesse Terefe; Lukwas, Andu Zakaria Wani; Beketie, Kassahun Ture; Ayal, Desalegn Yayel (Elsevier, 2024)
The Sudd Wetland, which supports millions of pastoralists and farmers, as well as the internationally renowned Ramsar Wetlands, are under pressure from population growth and climate change extremes such as flooding and drought. Using the Climate Hazards Group Infrareds Precipitation with Station (CHIRPS) and Climate Research Unit (CRU-TS4.06) datasets, this study investigates the spatiotemporal trend and variability of precipitation and temperature. As a result, descriptive statistics were used to describe the spatiotemporal behavior of precipitation and temperature. The Rotated Empirical Orthogonal Function (REOF) was used to detect the spatiotemporal variability of precipitation. The Pearson correlation method was used to investigate the relationship between Sea Surface Temperature (SST) and precipitation. The results revealed that Sudd-wetland receives 910 mm mean spatial annual precipitation and experienced 36 ◦C mean annual temperature with high spatiotemporal variations. It receives the highest precipitation in the summer season followed by autumn and spring. The precipitation amount decreases towards the north in all seasons. In both the summer and winter seasons, observed rainfall variability corresponds substantially to ENSO variability. In contrast, the spring and autumn seasons are more connected with Atlantic and Indian Ocean Sea surface temperature gradients. Alternatively, the Sudd wetland has been affected by prolonged drought and frequent flood events. The prolonged drought linked with the shrinking of the wetland are potential threat to the farmers and pastoralists to adapt to the changing climate. Hence, it is imperative to systematically analyze the wetland ecosystem from different dimensions and adjust the livelihood settings of the people to less climate-sensitive activities. Therefore, we suggest in-depth drought and flood risk evaluation and implementation of a realistic adaptation strategy to sustain the ecological and economic benefit of the wetland.